“The Incarnation” in the Horizon of Gadamerian Hermeneutics - LI, Lin (Journal of Research for Christianity in China (JRCC), 2026)
Scholars have proposed two interpretive approaches—theological and phenomenological—to Gadamer’s concept of “incarnation.” Yet neither fully implements his principle of the “fusion of horizons” leading to interpretations that deviate from his original intent. Employing Gadamer’s own hermeneutic methodology, this paper systematically demonstrates that “incarnation” constitutes a universally applicable interpretive framework, rooted fundamentally in the hermeneutic structure wherein truth emerges through historicity. By analyzing the ontological significance of “incarnation” as a metaphor, its universal hermeneutic transformation in Bultmann’s “demythologization,” and its philosophical function as an interpretive model, the study reveals how this framework mediates the tension between finitude and infinitude, history and truth. It further highlights Gadamer’s theoretical originality in grounding his approach in a “hermeneutic stance” rather than in merely theological or phenomenological positions.